2005
DOI: 10.1016/j.ijgo.2004.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumor necrosis factor alpha receptors p55/p75 ratio and ovarian cancer detection

Abstract: Serum TNF alpha p55/p75 ratio showed promising value in ovarian cancer detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…(20,21) Expression of TNF-α and its receptors has been reported in esophageal, (22) prostatic, (23) follicular thyroid, (24) skin (25) and ovarian (26) cancers. TNF-α has also been described as an important promoter of cancer in different breast cancer cell lines, such as and MCF10A.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(20,21) Expression of TNF-α and its receptors has been reported in esophageal, (22) prostatic, (23) follicular thyroid, (24) skin (25) and ovarian (26) cancers. TNF-α has also been described as an important promoter of cancer in different breast cancer cell lines, such as and MCF10A.…”
mentioning
confidence: 99%
“…(17) Several reports have stated that overexpression of p21 in breast carcinoma has been associated with accumulation of mtp53, (18,19) considered to be an indicator of poor prognosis. (20,21) Expression of TNF-α and its receptors has been reported in esophageal, (22) prostatic, (23) follicular thyroid, (24) skin (25) and ovarian (26) cancers. TNF-α has also been described as an important promoter of cancer in different breast cancer cell lines, such as MCF-7 (27) and MCF10A.…”
mentioning
confidence: 99%
“…Higher expressions of TNF- α have been reported in various tumour tissues [ 22 , 24 , 28 , 35 , 36 ]. TNF- α expression and its action have also been reported in esophageal cancer [ 37 ], ovarian cancer [ 38 , 39 ], breast cancer [ 40 ], and follicular thyroid cancer as well [ 41 ]. The present study also found a significant inverse correlation between the circulating levels and tumoural protein expression of TNF- α .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ovarian cancer cells had the capacity for spontaneous secretion of more sTNF-R1, but less receptor type 2 [24]. Additionally, serum TNF-R1 level correlated with morphological ultrasound score and CA125 [22]. The observations made in Burger's study [25] showed a relationship between levels of CA125, sTNF-R1 and sTNF-R2 and risk of progression of epithelial ovarian malignancies.…”
Section: Discussionmentioning
confidence: 99%